Analisis Pemenuhan Indikator Pembayaran Kapitasi pada Fasilitas Kesehatan Tingkat Pertama di Surabaya - Delvia Widaty (Universitas Airlangga, 2017)
Lack of patient visits to FKTP causes capitation not being optimally utilized. The purpose of this research is to analyze the causes of the unfullfilled capitation payment indicators based on fulfillment of service commitment at FKTP. The type of research used is observational with cross sectional design. Approach in the research is quantitative and qualitative. The research used total sampling, where population is secondary data covering result of indicator achievement from 62 Puskesmas, 31 DPP, and 97 Klinik Pratama in Surabaya. This research concluded that indicator of AK and RPPB at FKTP still not fulfill target of safe zone. AK can be caused by the lack of participants’ knowledge of FKTP services, limited resources, and BPJS Kesehatan online application that sometimes have interruptions. FKTP needs to provide promotions and education to participants’, add resources and provide training to staff, advocate with health offices, and cooperation with other parties to help provide facilities. Whereas the target indicator of RPPB has not been achieved due to lack of socialization of Prolanic. FKTP expected to be able to run activities that are promotive and preventive in groups. Keywords: capitation, capitation payment indicators based on fulfillment of service commitment, FKTP